KEARIFAN LOKAL DAN PARTISIPASI PERSEKUTUAN DAYAK KALIMANTAN TIMUR DALAM MENGHADAPI BENCANA KEBAKARAN HUTAN DAN LAHAN - Dirhamsyah, Dirhamsyah; Utama, Diar Budi; Widyaningrum, Nrangwesthi; Widana, I Dewa Ketut (Universitas Medan Area, 2020)
Balikpapan City is a buffer city for the for the new National Capital in the Province of East Kalimantan, which is not spared from forest and land fires. In tackling forest and land fires the actors who play a role are the community. Strengthening community institutions, in this case, the East Kalimantan Dayak Alliance, provides a stimulus for the development of disaster management in the regions. But this is not in line with what is expected. Often these customary institutions are not involved in development planning so there are many records for the government so that the involvement and representation of indigenous peoples can be accommodated. This study aims to analyze the culture of local wisdom and approach of participation of the East Kalimantan Dayak Alliance in Balikpapan City in dealing with forest and land fire disasters. The research approach used in this study is a qualitative method using a purposive sampling technique. Data obtained through interviews, observations and documentation. The results showed that local wisdom was reflected in long-standing living habits in managing land. The Dayak community has a quick response in extinguishing fires and has active participation in fighting forest and land fires.